2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7353847
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of contact forces and floating base kinematics of a humanoid robot using only Inertial Measurement Units

Abstract: A humanoid robot is underactuated and only relies on contacts with environment to move in the space. The ability to measure contact forces and torques enables then to predict the robot dynamics including balance. In classical cases, a humanoid robot is considered as a multi-body system with rigid limbs and joints and interactions with the environment are modeled as stiff contacts. Forces and torques at contacts are generally estimated with sensors which are expensive and sensitive to calibration errors. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…This is due to the large part of redundancy which lies in these measurements. Indeed, we have shown that the IMU alone is able to reconstruct the center of pressure of contact forces relatively accurately when coupled with our model [18]. The idea here is to take profit from this redundancy in order to rebuild an additional variable, the overall external force and moment which are not directly sensed.…”
Section: Description Of the Estimatormentioning
confidence: 97%
See 1 more Smart Citation
“…This is due to the large part of redundancy which lies in these measurements. Indeed, we have shown that the IMU alone is able to reconstruct the center of pressure of contact forces relatively accurately when coupled with our model [18]. The idea here is to take profit from this redundancy in order to rebuild an additional variable, the overall external force and moment which are not directly sensed.…”
Section: Description Of the Estimatormentioning
confidence: 97%
“…Indeed, the orientation and the velocity of the floating base are also subject to external forces, especially in the case of an unpredicted contact with the environment [18], [3]. In fact, several advanced methods for reconstructing the floating base kinematics actually use the data of external forces to reconstruct reliably the state of the robot [20], [2].…”
Section: Introductionmentioning
confidence: 99%
“…When there is an external tactile perturbation (user applies forces to the arm), e.g. t = [5,7]s (1a), the robot reacts to the tactile event and changes its position (1b), as soon as the external perturbation is removed, e.g. t = 8s the robot returns to its original position smoothly.…”
Section: F Torque Resolvermentioning
confidence: 99%
“…The interaction is repeated several times (t = [11,26]s), generating changes reflected in the joint position of the robot. We provide a video 7 to illustrate these behaviors in our robot TOMM using the proposed approach.…”
Section: F Torque Resolvermentioning
confidence: 99%
See 1 more Smart Citation